Powder X-ray structural studies and reference diffraction patterns for three forms of porous aluminum terephthalate, MIL-53(A1). Issue 3 (September 2019) - Wong-Ng, W.; Nguyen, H. G.; Espinal, L.; Siderius, D. W.; Kaduk, J. A.
Abstract : Powder X-ray diffraction patterns for three forms of MIL-53(Al), a metal organic framework (MOF) compound with breathing characteristics, were investigated using the Rietveld refinement method. These three samples are referred to as the MIL-53(Al)as-syn (the as synthesized sample), orthorhombic, Pnma, a = 17.064(2) Å, b = 6.6069(9) Å, c = 12.1636(13) Å, V = 1371.3(2) Å 3, Z = 4), MIL-53(Al)LT-H (low-temperature hydrated phase, monoclinic P2 1 / c, a = 19.4993(8) Å, b = 15.2347(6) Å, c = 6.5687(3) Å, β = 104.219(4) °, V = 1891.55(10) Å 3, Z = 8), and MIL-53(Al)HT-D (high-temperature dehydrated phase, Imma, a = 6.6324(5) Å, b = 16.736(2) Å, c = 12.840(2), V = 1425.2(2) Å 3, Z = 4). The crystal structures of the "as-syn" sample and the HT-D sample are confirmed to be the commonly adopted ones. However, the structure of the MIL-53(Al)LT-H phase is confirmed to be monoclinic with a space group of P2 1 / c instead of the commonly accepted space group Cc, resulting in a cell volume double in size. The structure has two slightly different types of channel. The pore volumes and pore surface area were estimated to be 0.11766 (8) cm 3 /g and 1461.3(10) m 2 /g for MIL-53(Al)HT-D (high-temperature dehydrated phase), and 0.08628 (5) cm 3 /g and 1401.6 (10) m 2 /g for MIL-53(Al)as-syn phases, respectively. The powder patterns for the MIL-53(Al)as-syn and MIL-53(Al)HT-D phases are reported in this paper.